2010
DOI: 10.3758/brm.42.1.292
|View full text |Cite
|
Sign up to set email alerts
|

Video context-dependent recall

Abstract: Many theories of episodic memory include mechanisms involving contextual processes, such as contextual associations and contextual cuing (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
85
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 57 publications
14
85
1
Order By: Relevance
“…The effect size of reinstatement was somewhat smaller in the present study, relative to effects found with video contexts (Smith & Manzano, 2010), suggesting that richer contexts, such as those that include sound and motion, may evoke greater contextdependency than we found with still photos of contexts. The context reinstatement effect was marginally greater for incidental contexts than for supportive contexts.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The effect size of reinstatement was somewhat smaller in the present study, relative to effects found with video contexts (Smith & Manzano, 2010), suggesting that richer contexts, such as those that include sound and motion, may evoke greater contextdependency than we found with still photos of contexts. The context reinstatement effect was marginally greater for incidental contexts than for supportive contexts.…”
Section: Discussioncontrasting
confidence: 91%
“…Studies where recall was better under context-reinstated conditions used various manipulations of environmental contexts, including underwater vs. on dry land (Godden & Baddeley, 1975), different laboratory rooms (McDaniel, Anderson, Einstein, & O'Halloran, 1988;Smith, 1979;Smith, Glenberg, & Bjork, 1978), and videos of environments (Smith, Handy, Angello, & Manzano, 2014;Smith & Manzano, 2010). Although Smith and Vela's meta-analysis (2001) showed that physical environmental manipulations have reliable effects on memory, the average effect size for such studies is modest (d = 0.28); in contrast, context reinstatement effect sizes for videos of environmental contexts are large (d > 1.0).…”
mentioning
confidence: 99%
“…Reinstating the encoding context did not modulate either memory performance or ERPs, which could result from a number of different mechanisms, including encoding processes such as overshadowing or retrieval processes such as outshining, which reduce the effectiveness of reinstated context cues (Smith, 1988; Smith & Manzano, 2010). Overshadowing occurs when contextual cues are less effective because multiple targets (e.g., words) are encoded in the same context during encoding (overloaded cue).…”
Section: Discussionmentioning
confidence: 90%
“…Despite the clear rationale underlying these predictions, as well as the fact that context-mediated facilitation of target memory is widely found when tested by free or cued recall (e.g., Parker, & Gellatly, 1997;Smith, & Manzano, 2010), CEs are difficult to produce reliably in recognition experiments (Hollingworth, 2006;Smith, & Manzano, 2010;Rutherford, 2000). Inconsistencies between studies that report CEs in recognition memory (e.g., Hollingworth, 2006;Russo, Ward, Geurts, & Scheres, 1999) and others that do not (e.g., Godden, & Baddeley, 1980;Murnane, & Phelps, 1993 contributed to Hanczakowski et al, (2014) proposition that while context reinstatement does reliably affect recognition processes, the effect is subtle and therefore not always detected by the presumably insensitive measure of recognition discrimination.…”
Section: Introductionmentioning
confidence: 99%